Value of Routine Gastrografin Upper Gastrointestinal Study After Sleeve Gastrectomy - Vitello, Dominic J. (JAMA Surg, 2018)
This study examines the effectiveness and cost of gastrografin upper gastrointestinal imaging test performed on patients after a laparoscopic sleeve gastrectomy.